Effects of integrated use of grass strip and soil bund on soil properties, Southern Ethiopia - Solomon Umer; Abebayehu Aticho; Endalikachew Kiss (Brawijaya University, 2019)
Soil degradation is the major environmental and agricultural production problem in the highlands of Ethiopia. The objectives of the study were to examine farmers’ use of grass strip and soil bund to minimize soil degradation, and effects of grass strip and soil bund on basic soil properties. Structured questionnaire survey and field observations were conducted to collect data on farmers’ use of grass strips and soil bund to minimize soil erosion, improve soil fertility and crop productivity. Simultaneously, composite soil samples were collected from croplands treated with both grass strip and soil bund, and the adjacent lands treated with soil bund only. The statistical result indicates respondents sex, marital status, educational level, erosion degree, access to conservation information, contact with extension workers, and trainings were significantly (P < 0.05) and positively affect the use of grass strips while livestock and land holding sizes were significantly (P < 0.05) and negatively affect farmers use of grass strip. The interaction of land management practices (grass strip and soil bund) and slope positions was significantly (P < 0.05) affects soil clay fractions and moisture, the highest amounts was observed at lands managed with grass strip situate at lower slope position. Similarly, soil organic matter, total nitrogen, available phosphorus, and cation exchange capacity were significantly (P < 0.05) influenced by the combined effects of land management practices and slope positions, highest quantity of these properties were observed lands managed with a grass strip and soil bund in lower slope position. Hence, integrated use of soil bund with grass strip has a meaningful contribution for selected soil property improvement that enhances soil fertility and crop productivity.